Penerapan Metode AHP-TOPSIS Dalam Menentukan Mahasiswa Lulusan Terbaik Pada Prodi Keperawatan UMKT Berbasis Web - Raenald Syaputra; Hamada Zein; Ari Ahmad Dhani; Bulan Suci Cahayawati; Faldy Alfareza Pambudi; Siti Muawwanah; Raihan Nabil; Bima Satria; Hery Kurniawan; Vito Junivan Rivaldo; Manda Rela Istiantoko (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study utilizes the AHP-TOPSIS method to determine the best graduating students in the nursing program. Evaluation criteria include GPA, duration of study, achievements, and final projects. The results indicate that GPA and achievements significantly influence the assessment of graduates. The use of the AHP-TOPSIS method demonstrates consistency, yet it's important to note that similar results don't always guarantee equivalence between the two methods. This study confirms the reliability of the method in evaluation, however, suggestions for future research include expanding the sample size and considering additional factors to enhance validity and reliability.